2021
DOI: 10.1038/s41380-021-01024-1
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 protein is a key molecular effector in the transition from normal to PTSD-like fear memory

Abstract: Moderate stress increases memory and facilitates adaptation. In contrast, intense stress can induce pathological memories as observed in post-traumatic stress disorders (PTSD). A shift in the balance between the expression of tPA and PAI-1 proteins is responsible for this transition. In conditions of moderate stress, glucocorticoid hormones increase the expression of the tPA protein in the hippocampal brain region which by triggering the Erk1/2MAPK signaling cascade strengthens memory. When stress is particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 81 publications
3
19
0
Order By: Relevance
“…Once MR binds to its ligand aldosterone, the MR configuration changes can occur. It can activate the nuclear localization signal, make the activated receptor–ligand complex quickly transfer to the nucleus, participate in the reaction of gene promoter or interact with other transcription factors, and induce the activation or inhibition of transcription and to regulate MR-related signaling pathways and a variety of physiological and pathological responses ( Bouarab et al, 2021 ). Our experimental results showed that compared with the sham group, the expression of MR was increased in the HIRI group ( p ˂ 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Once MR binds to its ligand aldosterone, the MR configuration changes can occur. It can activate the nuclear localization signal, make the activated receptor–ligand complex quickly transfer to the nucleus, participate in the reaction of gene promoter or interact with other transcription factors, and induce the activation or inhibition of transcription and to regulate MR-related signaling pathways and a variety of physiological and pathological responses ( Bouarab et al, 2021 ). Our experimental results showed that compared with the sham group, the expression of MR was increased in the HIRI group ( p ˂ 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as furin and plasmin regulate synaptic plasticity and the fibrinolytic system, an impaired tissue-type plasminogen activator (tPA)/PAI-1 ratio, may lower the resilience for both PTSD and COVID-19. Indeed, severe COVID-19 and impaired fear extinction were associated with tPA/PAI-1 dyshomeostasis (Bouarab et al, 2021;Zuo et al, 2021).…”
Section: Furin Cleaving Site and Ptsdmentioning
confidence: 99%
“…et al, 2016). Both severe COVID-19 and PTSD were associated with upregulated PAI-1, a negative tPA regulator, indicating that targeting this protein may be therapeutic for both diseases (Cesari et al, 2010;Idell et al, 2017;Bouarab et al, 2021). Indeed, PAI-1 has been identified as a potential target in COVID-19 and its antagonists, such as statins, are currently in clinical trials (NCT04634799) (NCT04472611) (Bouarab et al, 2021;Kellici et al, 2021; Figure 2).…”
Section: The Virus and Fibrinolytic Systemmentioning
confidence: 99%
See 2 more Smart Citations